1999
DOI: 10.1006/dbio.1999.9232
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for theXrcc1DNA Base Excision Repair Gene during Early Mouse Development

Abstract: Surveillance and repair of DNA damage are essential for maintaining the integrity of the genetic information that is needed for normal development. Several multienzyme pathways, including the excision repair of damaged or missing bases, carry out DNA repair in mammals. We determined the developmental role of the X-ray cross-complementing (Xrcc)-1 gene, which is central to base excision repair, by generating a targeted mutation in mice. Heterozygous matings produced Xrcc1-/- embryos at early developmental stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
227
0
10

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(243 citation statements)
references
References 66 publications
6
227
0
10
Order By: Relevance
“…Sp1 is generally considered as a transcriptional activator; however, as demonstrated in many previous studies, Sp1 may also function as a transcriptional inhibitor, repressing gene transcription in certain promoter contexts (Pagliuca et al, 1998;Shou et al, 1998;Dean et al, 2000;Li and Ou, 2001;Won et al, 2002). As XRCC1 plays important roles in BER (Thompson et al, 1990;Tebbs et al, 1999;Weinfeld et al, 2001;Caldecott, 2003), reduced expression of the protein would be expected to impair BER ability and hence increase the risk of lung cancer.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Sp1 is generally considered as a transcriptional activator; however, as demonstrated in many previous studies, Sp1 may also function as a transcriptional inhibitor, repressing gene transcription in certain promoter contexts (Pagliuca et al, 1998;Shou et al, 1998;Dean et al, 2000;Li and Ou, 2001;Won et al, 2002). As XRCC1 plays important roles in BER (Thompson et al, 1990;Tebbs et al, 1999;Weinfeld et al, 2001;Caldecott, 2003), reduced expression of the protein would be expected to impair BER ability and hence increase the risk of lung cancer.…”
Section: Discussionmentioning
confidence: 97%
“…As a scaffold protein in BER, the X-ray repair cross-complementing 1 (XRCC1) assembles a DNAprotein complex at the damage site with poly(ADPribose) polymerase, DNA polymerase-b and DNA ligase IIIa to complete the repair process (Weinfeld et al, 2001;Caldecott, 2003). The importance of XRCC1 in maintaining genomic stability is indicated by an increased frequency of spontaneous chromosome aberrations and deletions in XRCC1 mutant cells and by embryonic lethality in XRCC1 knockout mice (Thompson et al, 1990;Tebbs et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…XRCC1 null mouse line XRCC1 gene knockout in mice results in embryonic lethality, demonstrating it is essential for development (Tebbs et al, 1999). However, it is problematic to study any adult phenotype that may be the result of XRCC1 deletion.…”
Section: Xrcc1 Mouse Model Developmentmentioning
confidence: 99%
“…Cells lacking the gene product are hypersensitive to ionizing radiation, hydrogen peroxide, camptothecin and alkylating agents (reviewed by Caldecott, 2003). In addition, mutant cells show elevated frequency of spontaneous chromosomal aberrations and deletions, and null mutant mice exhibit an embryonic lethal phenotype indicating the importance of XRCC1 for genetic stability (Tebbs et al, 1999). A recent study has shown that XRCC1 is required for efficient DNA SSB repair (Brem and Hall, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…X-ray repair cross-complementing protein-1 (XRCC1) was the first human gene product isolated that mediates the cellular response to ionizing radiation (15). This protein is apparently essential and required for the BER pathway (16). Recent investigations demonstrated specific interactions of XRCC1 with Pol ␤, DNA ligase III (Lig III), and PARP-1 (13,(17)(18)(19)(20).…”
mentioning
confidence: 99%